IMPROVING READING COMPREHENSION THROUGH RECIPROCAL TEACHING TECHNIQUE - Rama Arisandi; Imro'atul Husna Afriani; Devi Novitasari (Universitas PGRI Palembang, 2025)
This study investigated the effectiveness of the reciprocal teaching method in enhancing students’ reading comprehension. Employing a quasi-experimental quantitative design, it utilized descriptive texts as instructional materials and analyzed data through pre- and post-tests using JASP software. Normality test results showed significance values of 0.083 (pre-test) and 0.735 (post-test), indicating normally distributed data. Homogeneity tests yielded significance values of 0.849 and 0.108, suggesting equal variances between groups. An independent samples t-test revealed no significant difference in pre-test scores (p = 0.383), but a significant improvement in post-test results (p < 0.001), highlighting the positive influence of reciprocal teaching on reading comprehension and metacognitive skills. Conducted at a junior high school in Banyuwangi, the study involved 30 students 16 in the experimental group and 14 in the control group. In addition to assessing instructional outcomes, the research also explored the broader educational benefits of the method.